2023
DOI: 10.1111/jgh.16275
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Helicobacter pylori infection leads to elevated fasting plasma glucose level: A retrospective cohort study based on a nondiabetes Chinese population

Abstract: Author contributions: SJZ made great contributions to the concept, design and data acquisition of the article. NNY and YC was mainly involved in data analysis. XDY, BBG, and JW were involved in article writing. Financial support: No funding was received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…You N, Chen Y et al have indicated that H. pylori infection is an independent risk factor for increased fasting plasma glucose (FPG) levels in non-diabetic (DM) individuals. Persistent H. pylori infection leads to elevated levels of FPG[34].…”
Section: Disussionmentioning
confidence: 99%
See 1 more Smart Citation
“…You N, Chen Y et al have indicated that H. pylori infection is an independent risk factor for increased fasting plasma glucose (FPG) levels in non-diabetic (DM) individuals. Persistent H. pylori infection leads to elevated levels of FPG[34].…”
Section: Disussionmentioning
confidence: 99%
“…However, Helicobacter pylori infection is not related to obesity-related parameters, glucose tolerance, or systolic blood pressure [13].There are also studies with opposing conclusions, which explored the relationship between Helicobacter pylori infection and fasting plasma glucose (FPG) levels in a non-diabetic population. The study found that Helicobacter pylori infection is an independent risk factor for increased FPG levels, and persistent infection can lead to increased levels of FPG and triglycerides/high-density lipoprotein (TG/HDL), which could be risk factors for diabetes [14].Recent research findings on the association between Helicobacter pylori infection and insulin resistance and metabolic syndrome have been contradictory. Therefore, a comprehensive meta-analysis was conducted, which included 22 studies involving 206,911 subjects.…”
Section: Introductionmentioning
confidence: 99%